Maksym Wyznawca, Ambiguum 5 (CPG 7705.1: Ambigua ad Thomam 5) - Kochańczyk-Bonińska, Karolina; Kosmulska, Bogna (Vox Patrum, 2025)
Translation into Polish of the work: Maximus the Confessor, Ambiguum 5.